The Effect of Magnetic Abrasive Finishing on the Flat Surface for Ferromagnetic and non-Ferromagnetic materials - Kadhum, Ali H; Hamad, Yahya M; Naif, Nazar Kais M. (Nahrain University College of Engineering Journal, 2015)
Magnetic Abrasive Finishing (MAF) is an advanced finishing method, which improves the quality of surfaces and performance of the products. The finishing technology for flat surfaces by MAF method is very economical in manufacturing fields an electromagnetic inductor was designed and manufactured for flat surface finishing formed in vertical milling machine. Magnetic abrasive powder was also produced under controlled condition. There are various parameters, such as the coil current, working gap, the volume of powder portion and feed rate, that are known to have a large impact on surface quality. This paper describes how Taguchi design of experiments is applied to find out important parameters influencing the surface quality generated during MAF method. In the experimental part, two types of materials from non-ferromagnetic and ferromagnetic (Aluminum alloy 7020 and stainless Steel 410 respectively) were considered with different parameters. Regressions models based on statistical-mathematical approach were obtained by using SPSS software for two materials.